Pengaruh Entrepreneurial Mindset Dan Kreativitas Pengusaha Melalui Implementasi Teknologi Terhadap Keberlanjutan Usaha (Studi Kasus Mitra Usaha Putra Ardana Farm Malang) - Ardana, Erico Janu; Khalikussabir, Khalikussabir; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of entrepreneurial mindset and creativity on business sustainability among Putra Ardana Farm Malang business partners. The application of entrepreneurial mindset and creativity in each individual is proven to be beneficial in maintaining and developing business sustainability. The research method used in this study was a quantitative approach, with data collection techniques in the form of printed questionnaires distributed to 45 Putra Ardana Farm business partners. The results of this study indicate that entrepreneurial mindset has a positive and significant effect on technology adoption and business termination. Creativity has a positive and significant effect on technology adoption but not on business termination. Furthermore, technology implementation does not mediate the relationship between entrepreneurial mindset and business interest or creativity on business desire. The implications of this study explain that Putra Ardana Farm needs to continue developing entrepreneurial mindsets and creativity for its partners to create more sustainable businesses. Keywords: Entrepreneurial Mindset, Creativity, Technology Implementation, Business Sustainability, Putra Ardana Farm